2016
DOI: 10.1002/cjce.22618
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and modelling of a maldistributed Trickle Bed Reactor

Abstract: A Trickle Bed Reactor equipped with a non‐ideal distribution tray is investigated. First, a non‐ideal co‐current trickling flow of nitrogen and heptane, induced by a partially plugged tray, is characterized experimentally using the γ‐tomography technique. Resulting liquid saturation data are used to validate the Euler‐Euler CFD model developed in previous work of Solomenko et al.[16] on a 3D realistic flow. The resulting 3D CFD model is then coupled with simple isothermal kinetics of heteroatom removal of heav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 38 publications
(80 reference statements)
0
6
0
Order By: Relevance
“…There is certainly no escape from conducting well‐thought and reliable experimental studies to characterize the hydrodynamics prevailing inside packed‐bed reactors. However, the associated restrictions and difficulties have limited the application of experimental methods to small laboratory‐scale setups, narrow operating ranges, and generally to cold fluid conditions . Therefore, procurement of a validated first‐principle‐based model can greatly enhance our understanding of the multiphase flow hydrodynamics in packed beds especially with an ambition to help in the scale up.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is certainly no escape from conducting well‐thought and reliable experimental studies to characterize the hydrodynamics prevailing inside packed‐bed reactors. However, the associated restrictions and difficulties have limited the application of experimental methods to small laboratory‐scale setups, narrow operating ranges, and generally to cold fluid conditions . Therefore, procurement of a validated first‐principle‐based model can greatly enhance our understanding of the multiphase flow hydrodynamics in packed beds especially with an ambition to help in the scale up.…”
Section: Introductionmentioning
confidence: 99%
“…So far Eulerian CFD models with appropriate closure laws were able to successfully predict bed overall pressure drop and liquid holdup for vertical gas–liquid cocurrent downflow packed beds . Meanwhile, application of a two‐fluid Eulerian CFD framework combined with the relative permeability closure model was limited to qualitative descriptions of the hydrodynamics of stationary tilted packed beds .…”
Section: Introductionmentioning
confidence: 99%
“…A modification to the capillary pressure correlation developed by Attou and Ferschneider was suggested by the authors to further validate their predictions. The mechanical dispersion forces together with the capillary pressure force were taken into account as the closure laws in the Eulerian multifluid model to simulate the liquid spreading and maldistribution in the vertical trickle bed reactor as well . Lappalainen et al showed that as long as the liquid phase flows through packed beds, both the capillary and mechanical dispersion mechanisms consistently exist; however, their relative significance is determined by the properties of the porous medium.…”
Section: Introductionmentioning
confidence: 99%
“…12 These experimental findings thus highlight the fact that cyclic operation can be regarded as a potential method for process intensification in offshore floating packed bed reactors extending it beyond the realm of conventional trickle beds where cyclic operation has been successfully applied to enhance mass transfer, improve phase distribution, reduce fines deposition, or control foam formation, to name just a few examples. [13][14][15] Several researchers successfully applied the Eulerian multifluid CFD model along with well-established interphase interaction forces as closure laws to predict bed overall pressure drop and liquid holdup in conventional vertical gas-liquid cocurrent downflow packed beds (i.e., trickle-bed reactors) under steadystate (i.e., iso-flow) [16][17][18][19][20][21][22][23][24][25] and unsteady-state cyclic operation. 17,26 Hamidipour et al 17 were able to precisely capture the transient hydrodynamic behaviors of trickle-bed reactors under gas, liquid, and gas/liquid alternating cyclic operations using an unsteady multifluid Euler framework combined with the closure laws developed by Attou et al 27 for fluid-solid drag forces and fluid-fluid interaction force.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation